Marketing research consumer behavior of hotel services - Besekei, E. (Journal of Economic Research & Business Administration, 2015)
The author cites the following stages of marketing research: goals and objectives of the research, the research method is selected, prepared sheet-based questionnaire, conducted a preliminary survey, changes were made to the list-based questionnaire was conducted sorting; collected information is defined representativeness sorting was an examination of the information, the analysis of the results. The purpose of marketing research is to collect and systematize information on consumer behavior for the preparation of the marketing strategy of the domestic hotel industry. The results of a marketing research on consumer behavior, the hotel business. In a review of the two types of customers: individuals and legal entities. Thus, a research identified two types of consumers.